# Scala: Flatten the parseresult (~) from combinators parser into List?

I wrote some parser from combinatory library. I want a generic function that transform any size of nest ~ into a list. How to do this ?

Here is my example of parser I use (my real parser has a very long chain ~ so I want to avoid my current solution which is in comment below).

```object CombinatorParser extends RegexParsers {

lazy val a = "a"
lazy val b = "b"
lazy val c = "c"
lazy val content = a ~ b ~ c // ^^ {case a~b => a::b::c::Nil work but I want something more general that work for any ~ length.
}

object CombinatorTesting {

def main(args:Array[String]) {
val testChar = "abc"
val output = CombinatorParser.parseAll(CombinatorParser.content, testChar)
println(output) // ((a~b)~c) but I want List(a,b,c)
}
}
```

This is a good (and fairly simple) application for the kind of generic programming techniques exemplified in shapeless.

```object CombinatorParser extends RegexParsers {
lazy val a = "a"
lazy val b = "b"
lazy val c = "c"
lazy val content = a ~ b ~ c
}
```

We can recursively define a type class that will flatten it's results as follows,

```import CombinatorParser._
```

First we define a trait which (abstractly) flattens an arbitrary match M to a List[String],

```trait Flatten[M] extends (M => List[String]) {
def apply(m : M) : List[String]
}
```

Then we provide type class instances for all the shapes of M that we're interested in: in this case, String, A ~ B and ParseResult[T] (where A, B and T are all types for which there are Flatten instances),

```// Flatten instance for String
implicit def flattenString = new Flatten[String] {
def apply(m : String) = List(m)
}

// Flatten instance for `A ~ B`. Requires Flatten instances for `A` and `B`.
implicit def flattenPattern[A, B]
(implicit flattenA : Flatten[A], flattenB : Flatten[B]) =
new Flatten[A ~ B] {
def apply(m : A ~ B) = m match {
case a ~ b => flattenA(a) ::: flattenB(b)
}
}

// Flatten instance for ParseResult[T]. Requires a Flatten instance for T.
implicit def flattenParseResult[T]
(implicit flattenT : Flatten[T]) = new Flatten[ParseResult[T]] {
def apply(p : ParseResult[T]) = (p map flattenT) getOrElse Nil
}
```

Finally we can define a convenience function to simplify applying Flatten instances to parse results,

```def flatten[P](p : P)(implicit flatten : Flatten[P]) = flatten(p)
```

And now we're ready to go,

```val testChar = "abc"
val output = parseAll(content, testChar)
println(output)          // ((a~b)~c) but I want List(a, b, c)

val flattenedOutput = flatten(output)
println(flattenedOutput) // List(a, b, c)
```

If you prefer a solution without generic programming...

```  def flatten(res: Any): List[String] = res match {
case x ~ y => flatten(x) ::: flatten(y)
case None => Nil
case Some(x) => flatten(x)
case x:String => List(x)
}

val testChar = "abc"
val output = CombinatorParser.parseAll(CombinatorParser.content, testChar).getOrElse(None)
println(flatten(output))
```